Investigation of the Effect of EMDR Therapy on Psychosomatic Symptoms and Early Malaptive Schemas: An Analysis of 5 Cases - Güler, Kahraman; Baysal, Elif Fulya (The European Research Journal, 2026)
Objective: This study examined the effects of Eye Movement Desensitization and Reprocessing (EMDR) therapy on psychosomatic symptoms and early maladaptive schemas.Methods: This study used a single-group pretest-posttest multiple case design, conducted without a control group. Five voluntary participants aged 18 and over were selected via purposive sampling. Data were collected through a Demographic Information Form, the Young Schema Questionnaire, and the Somatization Scale(33 items, derived from the MMPI).Results: All participants showed decreases in early maladaptive schemas and psychosomatic symptoms after EMDR therapy, indicating its effectiveness in reducing both cognitive and somatic distress.Conclusion: EMDR therapy appears effective in alleviating psychosomatic symptoms and maladaptive schemas. These findings support its clinical use and highlight the need for further research with larger samples.